Sustained censorship in RU (2026-06) (Russia) - Voidly (2026)
CRITICAL severity censorship detected in Russia. Confidence: 72%. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: RU-2026-0274
Keywords: censorship; RU; censorship; critical